Analysis of allelic expression patterns in clonal somatic cells by single-cell RNA–seq - Reinius, Björn; Mold, Jeff E; Ramsköld, Daniel; Deng, Qiaolin; Johnsson, Per; Michaëlsson, Jakob; Frisén, Jonas; Sandberg, Rickard (Nature genetics, 2016)
Rickard Sandberg and colleagues use allele-sensitive single-cell RNA–seq on primary mouse fibroblasts and human T cells to study clonal and dynamic monoallelic expression patterns. They find that the majority of random monoallelic expression of autosomal genes occurs transiently within individual cells rather than being stably inherited within clonally related cells. Cellular heterogeneity can emerge from the expression of only one parental allele. However, it has remained controversial whether, or to what degree, random monoallelic expression of autosomal genes (aRME) is mitotically inherited (clonal) or stochastic (dynamic) in somatic cells, particularly in vivo . Here we used allele-sensitive single-cell RNA–seq on clonal primary mouse fibroblasts and freshly isolated human CD8 + T cells to dissect clonal and dynamic monoallelic expression patterns. Dynamic aRME affected a considerable portion of the cells' transcriptomes, with levels dependent on the cells' transcriptional activity. Notably, clonal aRME was detected, but it was surprisingly scarce (<1% of genes) and mainly affected the most weakly expressed genes. Consequently, the overwhelming majority of aRME occurs transiently within individual cells, and patterns of aRME are thus primarily scattered throughout somatic cell populations rather than, as previously hypothesized, confined to patches of clonally related cells.